Are Developing Asia's Foreign Exchange Reserves Excessive? An Empirical Examination - Donghyun Park; Gemma Estrada (Asian Development Bank (ADB), 2009)
Developing Asian countries have accumulated foreign exchange reserves on an unprecedented scale in recent years. There is a growing consensus that Asia's reserves now substantially exceed the levels required for precautionary purposes or for self-protection against currency crisis. The central objective of our paper is to informally and formally test whether reserves in developing Asia have in fact reached excessive levels. Informal tests of reserve adequacy based on widely used rules of thumb such as the Greenspan-Guidotti rule unambiguously indicate the presence of sizable excess reserves. To test for excess reserves more formally, we use panel-data econometric analysis based on Edison (2003). Our estimation results indicate the presence of large and growing excess reserves since 2002. The results of both informal and formal tests thus confirm the popular belief that developing Asia now has excessive foreign exchange reserves. Therefore, the short-run policy challenge for Asian governments is to manage the region's burgeoning excess reserves more actively and use them more productively. One promising area of future research, brought to the fore by the global financial crisis, is to develop more nuanced measures of reserve adequacy that take into account the possibility of severe negative shocks.
hdl:11540/1823
Keywords: F31; 330; Foreign exchange reserve; Asia